Nivel de síntomas depresivos en estudiantes del programa de enfermería de la Universidad Antonio Nariño sede Neiva, durante el año 2022. - Robles Gutiérrez, Leidy Tatiana; Perdomo García, Luisa Fernanda (Universidad Antonio Nariño, 2023)
One of the mental health disorders that most affects individuals is depression; In addition, it is accompanied by numerous negative signs and symptoms such as stress, lack of motivation, changes in mood, concentration difficulties, insomnia and suicidal ideas. In the university population, a main management of these behaviors is estimated, due to their changes in lifestyle and different experiences that arise in their academic course. (1). Therefore, the nursing program of the Antonio Nariño University, Neiva, is included in order to identify the different symptoms through an instrument called the Beck Depression Inventory (BDI-2), which contains 21 items. The study will be carried out with the total population of students of the program belonging to the semester 2022-1. (two). With a quantitative, descriptive cross-sectional or prevalence approach, through virtual surveys by Google Forms, identifying cases of severe depression, risk factors, suicidal ideas, behavioral changes and a diagnosis of how the mental health of the nursing program is; In addition, it is sought that this project continue with the realization of a series of strategies, through active listening spaces, self-reflection programs and continuous accompaniment, as a result of mitigating this impact on society.